Australian Department Heads Under Howard: Career Paths and Practice Collected Articles from The Canberra Times - Malone, Paul (Australia and New Zealand School of Government (ANZSOG), 2006)
The articles in this collection were first published in the Canberra Times between 14 November 2005 and 22 April 2006 in a slightly different format. In some cases two articles were published on the one secretary. These have been combined into one and minor edits and corrections have been made. The articles have not been updated to take account of events since they were first published.